A Study of Community Knowledge Level Regarding the Dagusibu Program for Antibiotic Medicines in Penfui Timur Village - Mabu, Concitha Katarina Neno; Regaletha, Tadeus Andreas Lada; Upa, Nurul Fatmawati Pua; Purnasari, Cahyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Antimicrobial resistance, treatment failure, and higher healthcare expenditures are all consequences of inappropriate antibiotic usage, which continues to be a significant public health concern. The goal of the DAGUSIBU (Get, Use, Store, and Dispose of Medicines Properly) campaign is to increase public awareness and encourage sensible medication management. This study described community knowledge regarding the DAGUSIBU program for antibiotic medicines among residents of Penfui Timur Village, Kupang Tengah District, Kupang Regency. A descriptive quantitative study was conducted from March to April 2026 involving 99 respondents selected using cluster sampling. Data were collected using a validated structured questionnaire and analyzed descriptively. Knowledge was classified into good, moderate, and poor categories based on predetermined scoring criteria. Overall knowledge of the DAGUSIBU program and antibiotic use was categorized as moderate, with scores of 66.67% and 69.56%, respectively. The highest score was found in obtaining medicines (74.75%), whereas the lowest was in disposing of medicines (57.37%). Most respondents had a moderate level of knowledge. Community knowledge regarding the DAGUSIBU program was generally moderate. The low score for medicine disposal highlights the need for targeted educational interventions to improve appropriate disposal practices and support rational antibiotic use.